Investigation on machining performance of TiB2 and TiN coatings with modified cutting insert in AISI 1017 turning - Amirul, Zainal; Mohd Hafizu, Zakaria; Saiful Anwar, Che Ghani (IOP Publishing, 2020)
In the last decades machining methods have witnessed an advancement in both cutting tools' geometry and hard coatings, sometimes in combination with Ti-based coating. In the present study, the machining performance of adhesion resistant Ti-based coating materials with modified cutting insert on tool wear was investigated in turning AISI 1017 carbon steel. TiB2 and TiN hard coatings with similar layer thickness produced by physical vapor deposition (PVD) technique were considered as coating film for 1 mm thick tungsten carbide with Co binder cutting tools. The machining performance was evaluated mainly by surface roughness, cutting temperature and correlated in terms of tool wear. Through a set of experiments, modified cutting insert coated with TiB2 exhibited about 24-33% improvement in tool wear compared to TiN coated insert. The results from this study show that TiB2 coating can be used as coating material for cutting tool but further research on tribology and sustainability along with cutting dynamics study are prerequisites for commercial application of this coating material in the mainstream.